2013
DOI: 10.1021/jo302726m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Internal Trifluoromethyl Group on the Rhodium(II)-Catalyzed Reactions of Vinyldiazocarbonyl Compounds

Abstract: Incorporation of a trifluoromethyl group into the structure of 4-(alkoxycarbonyl)vinyldiazocarbonyl compounds greatly decreases the tendency of the carbenoid intermediates formed during Rh(II)-catalyzed reactions to undergo intermolecular processes. Instead, they are prone to experience intramolecular [1,5]- and [1,3]-electrocyclizations to produce reactive cyclopropenes and furans, and these are capable of further transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Early investigations by Davies et al 170173 indicated the catalytic formation of donor–acceptor cyclopropenes from a series of vinyldiazo compounds. Among them, cyclopropenes generated in situ from enoldiazo compounds were successfully trapped by cyclopentadiene to deliver the corresponding [2+4]-cycloadducts.…”
Section: Cpec Reactions Of Enoldiazo Compoundsmentioning
confidence: 99%
“…Early investigations by Davies et al 170173 indicated the catalytic formation of donor–acceptor cyclopropenes from a series of vinyldiazo compounds. Among them, cyclopropenes generated in situ from enoldiazo compounds were successfully trapped by cyclopentadiene to deliver the corresponding [2+4]-cycloadducts.…”
Section: Cpec Reactions Of Enoldiazo Compoundsmentioning
confidence: 99%
“…Quaternary carbon centers are frequently found as an important structural motif in various naturally occurring, biologically active compounds, so synthetic studies of such units have been extensively performed in recent years . Fluorinated compounds have also attracted great interest because fluorine often endows organic molecules with many important properties such as high lipophilicity, bioavailability, and metabolic stability. , However, very few methods for the construction of trifluoromethylated all-carbon quaternary centers have been reported, possibly because β-defluorination occurs, forming an alkene, when an anion is generated α to a CF 3 group. Until now, there have been a few examples of reactions that successfully prevent the defluorination of α-CF 3 carbanions and their equivalent building blocks, including reactions with aldehydes at low temperature, enol-mediated reactions, palladium-catalyzed allylic alkylation, − , and iridium/ruthenium-catalyzed Michael addition .…”
Section: Introductionmentioning
confidence: 99%